Karakteristik Adopter pada Masyarakat Nelayan Kampung Cipatuguran Palabuhanratu dalam Penerimaan Teknologi Baru - Pepi Rospina Pertiwi; Idha Farida; Rinda Noviyanti (Jurnal Penyuluhan, 2011)
In extension agriculture, the innovation introduction for goals is the important think especially if the innovation had appropriate with goals needed and its application to raising the goals welfare. This study aimed to explains the fisherman innovativeness level and the adopter characteristic category.   Explanatory research design with survey method were used to collect data. The location were choosen with purposively in Kecamatan Palabuhanratu, Kabupaten Sukabumi, Jawa Barat.  The population as a whole are all fisherman in Palabuhanratu, and  37 fisherman are chosen randomly as study samples. Data collection is using survey method, and are showed quantitivelly by frequently tabulation and bar chart. This study shows that the fisherman in Kampung Cipatuguran, Palabuhanratu is dominated by high-level in leaderships level, capital ownership, empaty level, abstraction level, dare to take a risk level,  futuristic level, partisipation level, and communication activity.  Base on asking all of respondents, the degree of innovation tryness was shown medium relatively, decision for adopt the innovation is relatively high, the fearness of take a risk is relatively high, the need of supporting agent of change is relatively high, the appropriate of take a decision is relatively low,  the equal of social relationship is relatively high and the relationship with informal leader was is relatively low.Key words: adopter, fisherman, innovation